Pengenalan Software Desain 3D Modelling Untuk Siswa SMK Bima Utomo Bs - Irwansyah Irwansyah; Khairani Puspita; Alfian Alfian (Universitas Pahlawan Tuanku Tambusai, 2022)
One way to improve the quality of education in schools is to implement an information system based on computer technology, one of which is to provide an understanding of the development of software technology. In today's digital era, software technology is one of the necessities for creating and planning products. In designing interior and exterior buildings, software is needed to plan buildings which were originally from sheets of work paper in the form of sketches but can only be made into 3D modeling. By introducing the role of 3D Modeling software technology as a supporter of student interest in learning so that it can improve achievement, student understanding and student interest in 3D Modeling Software. The form of community service activities carried out is counseling by presenting material about the introduction of 3d Modeling software which is developing and widely used in the current digital era and practicing tools on the software.